2018
DOI: 10.1136/bmj.k3310
|View full text |Cite
|
Sign up to set email alerts
|

Environmental toxic metal contaminants and risk of cardiovascular disease: systematic review and meta-analysis

Abstract: ObjectiveTo conduct a systematic review and meta-analysis of epidemiological studies investigating the association of arsenic, lead, cadmium, mercury, and copper with cardiovascular disease.DesignSystematic review and meta-analysis.Data sourcesPubMed, Embase, and Web of Science searched up to December 2017.Review methodsStudies reporting risk estimates for total cardiovascular disease, coronary heart disease, and stroke for levels of arsenic, lead, cadmium, mercury, or copper were included. Two investigators i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
264
4
12

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 357 publications
(294 citation statements)
references
References 97 publications
(62 reference statements)
14
264
4
12
Order By: Relevance
“…The results shown in Table (1) and Table (2) show a significant increase (P≤0.001) in the serum copper level of vascular patients of both sexes. This result is consistent with Chowdhury and his group 2018 [63] that copper helps increase the risk of vascular disease by promoting the LDL oxidation process, which in turn contributes to atherosclerosis, that is, its low level is positive towards the prevention of this injury. Overall, the high level of copper Has a harmful role in promoting and increasing the condition of oxidative stress by increasing the number of active oxygen in the case of free and not associated with protein or otherwise, as in this case has the ability to produce free radicals and the middle of the process of lipid peroxidation [64,65].…”
Section: Resultssupporting
confidence: 91%
“…The results shown in Table (1) and Table (2) show a significant increase (P≤0.001) in the serum copper level of vascular patients of both sexes. This result is consistent with Chowdhury and his group 2018 [63] that copper helps increase the risk of vascular disease by promoting the LDL oxidation process, which in turn contributes to atherosclerosis, that is, its low level is positive towards the prevention of this injury. Overall, the high level of copper Has a harmful role in promoting and increasing the condition of oxidative stress by increasing the number of active oxygen in the case of free and not associated with protein or otherwise, as in this case has the ability to produce free radicals and the middle of the process of lipid peroxidation [64,65].…”
Section: Resultssupporting
confidence: 91%
“…The presence of metals and metalloids (e.g., arsenic, chromium, lead, nickel) in e-cigarette aerosols is a major concern, given their serious health effects, including cancer (García-Esquinas et al 2014;Kuo et al 2017), cardiovascular disease (Chowdhury et al 2018;Moon et al 2012), renal damage (Suwazono et al 2006), and neurotoxicity (Sankhla et al 2017). Metals/metalloids may originate from the coil (Farsalinos et al 2015;Olmedo et al 2018) and from soldered joints and other parts of the device (Williams et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Tellez-Plaza et al demonstrated an association of urine cadmium with PAD [4]. A meta-analysis by Chowdhury et al, encompassing over 300,000 patients, recently reported that lead and cadmium are cardiovascular risk factors with a doseresponse relationship [24]. An environment-wide association analysis by Zhuang et al, in 2018, analyzed the NHANES data for predictors of PAD [25].…”
Section: Discussionmentioning
confidence: 99%